Using constraint programming for split delivery scheduling in scarce resource environment - Choosri N. (2014)
The research proposes a novel generic fleet scheduling for a split delivery with scarce resource problem. The research presents the problem in Constraint Satisfaction Problem (CSP) and further tackling it using Constraint Programming. The prototype system has been developed to evaluate the proposed method using problem statement case study from one of the large agricultural product supplier in the north of Thailand. The developed system deals with practical constraints including hard constraints e.g. vehicle capacity, time window, vehicle usage restriction and fleet constraints, and soft constraint which is a minimising of using subcontractor. The results showed a primary success of the proposed method in providing efficiency decision for agricultural transport planning. © 2011 IEEE.